Avaliação do destino do lixo em uma escola do campo no município de Igarapé-Miri - PENA, Raimunda Veronica Souza (2019)
environmental issues have become more intense as a result of some of the environmental crises experienced by the world. This has led many countries to unite to discuss the future of nations, and thus environmental education has emerged and with it the concept of sustainable development. Thus, countless actions and projects were carried out around the world, with the aim of raising the awareness of the world population about the importance of sustainable development. Currently, one of the main environmental problems we face is related to the high volume of solid waste produced and disposed of unduly in nature, due to the high consumption rate of the urban and rural population. Thus, the objective of this work is to analyze the destination given to the garbage in a school of the field, since we consider that it is, is the main auxiliary of environmental education and plays an extremely important role in this process. The methodology used is qualitative, through a case study. the application of forms for students in the final years of elementary school and interviews with managers and teachers, as well as observation, capturing of images and notebook were carried out. The results obtained indicated the most used destination for solid and organic waste, the types of waste produced both in the school premises and in the communities where the students are inserted, in addition to the separation coefficient used in the communities and the approach adopted by the school to work on the problem. It has been found that the school produces a daily amount of waste and most are discarded improperly. One of the main reasons is that the school's actions on this issue are superficial, the projects are very small and most of the time they are restricted in informal conversations with students and family and posters spread around some spaces of the school. In addition, the lack of public policies is another factor that contributes to the problem, since there is no community or state action in the community that allows alternatives for the residents.